MARKET AND MARKET MECHANISM VERSUS REFLEXION - Natasa Rovenska (European Scientific Journal, ESJ, 2014)
The article explains the exchange of information between subjects in a society. Exchange of information is explained on the example of a logical system with one input, one output and three control variables. The parallel with the example of the logical system is used to explain how a new technology and a new product are put into practice. The role that plays the interaction between a society and its subjects when a new technology and a new product are put into practice is explained in conclusion.